Developing an instructional module of 'digital dentistry' for undergraduate prosthodontics curriculum - Shuchi Tripathi; P.S. Manoharan; Suhasini Nagda (Elsevier, 2024)
Purpose: To prepare a module on 'Digital Dentistry", which can be used to sensitize dental undergraduate students during their final year Prosthodontics curriculum. Methods: Ethical approval (167/Ethics/2022) was taken from the Institution before starting the study. Need assessment was achieved using focused group discussion (Online Zoom meeting) of various stakeholders of the Department of Prosthodontics of the institution. A preliminary module content was prepared in google questionnaire form after thorough literature review by the research team and final content was developed using modified Delphi technique in 3 questionnaire rounds with the help of 27 experts. Result: Thematic analysis of Need Assessment focussed group discussion led to the emergence of both theoretical and practical aspect of learning in digital dentistry. The final module was developed with the process followed in modified Delphi technique. Conclusion: Within the limitations of the study the module of Digital dentistry was developed which can be implemented in most of the dental institutes depending on the resources and available infrastructure.